Designing and Controlling of Wireless Robot for Data Collection by Using RF Communication - Nguyễn Chí Nhân; Trần Quốc Thanh; Nguyễn Tuấn Kiệt (Journal of Technical Education Science, 2012)
In this paper, we designed the wireless robot for data collection and controlled the robot direction using Personal Computer (PC). The control unit in robot controls the robot direction according to the commands given from the control program on PC by using RF wireless communication. There, AVR (ATmega 16) microcontroller and HM-TR transceiver are used. Microcontroller is interfaced to PC through UART communication using MAX 232 level converter. The robot will collect data such as: temperature, humidity, pressure and will transmit this data to the control program on PC by using RF transmitter. In addition, robot can move in forward, back, left, right directions according to the control program on PC. Besides, we used the camera to locate the robot.